2007
DOI: 10.1243/14644207jmda65
|View full text |Cite
|
Sign up to set email alerts
|

Study of the selective laser sintering of polycarbonate and postprocess for parts reinforcement

Abstract: Polycarbonate (PC) powder, a common and low-cost amorphous polymer, can be moulded easily by the process of selective laser sintering (SLS). However, the sintered parts cannot be used as functional parts because of their poor mechanical properties. In this article, epoxy resin was applied to improve the mechanical properties of PC SLS parts. Specimens for testing dimensional accuracy, tensibility, flexibility, and impact strength were made by SLS with 75-100 mm PC powder. Some of the specimens were posttreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 5 publications
1
31
0
Order By: Relevance
“…Similar results have been found by Shi et al [7], who post-treated polycarbonate (PC) specimens infiltrated with epoxy resin, showing great enhancement of mechanical properties. At the same time, they found that the average dimensional error of PC SLS specimens is not satisfactory, ranging from 6.67 to 13.6 per cent.…”
Section: Introductionsupporting
confidence: 88%
“…Similar results have been found by Shi et al [7], who post-treated polycarbonate (PC) specimens infiltrated with epoxy resin, showing great enhancement of mechanical properties. At the same time, they found that the average dimensional error of PC SLS specimens is not satisfactory, ranging from 6.67 to 13.6 per cent.…”
Section: Introductionsupporting
confidence: 88%
“…While [13] optimises the SLS parameters to build polyester lattice structures. Also experimentally, [14] and [15] examine the effect of preheating and respectively of part porosity and postprocessing on the mechanical properties of polyether and polycarbonate. Although complex and impractical, two-and three-dimensional analytical models still show severe limitations for direct quantitative predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, thermal properties of materials are of particular important factors determining the SLS processing parameters and part properties. Several amorphous polymers have been successfully used as SLS materials, such as polycarbonate (PC) (Childs et al, 1999;Ho et al, 1999;2002;Fan et al, 2005;Shi et al, 2007), polystyrene (PS) (Shi et al, 2004;Zheng et al, 2006), high impact polystyrene (HIPS) (Shi et al, 2008;Yang et al, 2009) and styrene-acrylonitrile copolymer (Yan et al, 2010). Ho et al (1999;2002;) did many works in exploring to make PC function plastic parts via SLS.…”
mentioning
confidence: 99%
“…They investigated the effect of laser energy density on the morphologies, densities and tensile strengths of PC SLS parts, attempting to make high density and strength parts by increasing laser energy density. Shi et al (2007) discussed the possibility of making PC functional parts via SLS from another angle. The green PC SLS parts with high dimensional accuracy and low strength were first fabricated, and then infiltrated with epoxy resin so that the mechanical properties were greatly enhanced.…”
mentioning
confidence: 99%